A structural model of educational attainment in Canada - Jörgen Hansen; Xingfei Liu (Institute for the Study of Labor (IZA), 2013)
In this paper, we develop and estimate a structural, dynamic model of schooling decisions using data extracted from the Canadian Youth in Transition Survey (YITS). The model incorporates forward-looking behavior and expectations about future benefits from investing in education. The results suggest that the effect of an increase in parental income on educational attainment is modest. For example, a 25 percent increase in parental income is predicted to increase post-secondary education (PSE) attendance by one percent only. However, our results indicate that financial resources, other than parental income, play a role in PSE enrollment. In particular, our model predicts that an increase in PSE tuition fees by 2,500 per grade level (for grade 13 and above) will reduce attendance in these grades by almost 9 percentage points for males and by 6.5 percentage points for females. We also simulate the impacts of changes in Programme for International Student Assessment (PISA) reading scores. Specifically, an increase of test scores with one standard deviation (which is comparable to the difference in average score for high school drop-outs and those with some PSE) increases PSE attendance by 10.2 percentage points for males and by 6.6 percentage points for females. At the same time, high school dropout rates are predicted to fall by 3.2 percentage points for males and by 2.8 percentage points for females. We also take advantage of the dynamics of the model and explore how a 25 percent increase in future wages for PSE students will affect current schooling decisions. This leads to an increase in PSE attendance by 2.2 percentage points for males and by 3.1 percentage points for females.
Keywords: J01; I21; 330; educational attainment; structural estimation; forward-looking behavior; parental income; tuition fees; cognitive ability